2005
DOI: 10.1007/s10903-005-3678-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Coping, and Health: A Comparison of Mexican Immigrants, Mexican-Americans, and Non-Hispanic Whites

Abstract: Mexican immigrants, Mexican-Americans, and non-Hispanic white Americans all face different stressors. Stress-coping strategies may vary for each group as well. We compared relationships among perceived stress, stress-coping strategies, and health-related quality of life (HRQL) in a rural sample of Mexican citizens living in the United States, Mexican-Americans, and non-Hispanic whites. Health-related quality of life and stress-coping styles varied among the three groups. Mexican citizens reported significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
134
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(148 citation statements)
references
References 43 publications
8
134
1
5
Order By: Relevance
“…Questions of life stressors were drawn from research on an array of health outcomes and stress (Campos, Schetter, Walsh, & Schenker, 2007;Dressler, 1996;Farley, Galves, Dickinson, & Perez, 2005;Wallace & Wallace, 2004). Not all questions in the survey are examined here.…”
Section: Methodsmentioning
confidence: 99%
“…Questions of life stressors were drawn from research on an array of health outcomes and stress (Campos, Schetter, Walsh, & Schenker, 2007;Dressler, 1996;Farley, Galves, Dickinson, & Perez, 2005;Wallace & Wallace, 2004). Not all questions in the survey are examined here.…”
Section: Methodsmentioning
confidence: 99%
“…Whites (Farley et al, 2005). Finally, the direct effect between duration of residence and BMI remained significant even after accounting for the six mediators, suggesting that other potential mediators should be explored in future research.…”
mentioning
confidence: 85%
“…Twelve studies [17,18,[52][53][54][55][56][57][58][59][60][61] reported that the turning to religion sub-scale loaded to a factor with at least one other sub-scale, three studies [62][63][64] reported that the turning to religion sub-scale formed its own separate factor, and five studies [21,[65][66][67][68] reported that the religion sub-scale did not have a sufficiently high loading with any other factor. As with the item-level analyses (Table 1), PCA was the most frequently used technique, with 9 of the 20 studies [18,[52][53][54]56,57,62,64,66] explicitly stating this method. Of the ten studies that mentioned the rotation method used, nine [18,21,[52][53][54][55]61,62,67] stated varimax, and one stated that they had used an oblique rotation [68].…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
“…As with the item-level analyses (Table 1), PCA was the most frequently used technique, with 9 of the 20 studies [18,[52][53][54]56,57,62,64,66] explicitly stating this method. Of the ten studies that mentioned the rotation method used, nine [18,21,[52][53][54][55]61,62,67] stated varimax, and one stated that they had used an oblique rotation [68]. Nine studies [17,21,58-60,63,65,67,68] only stated that they had used a factor analysis or exploratory factor analysis, and two studies had used a principal axis factor analysis [55,61].…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation